Photoproduction of the electron-positron pair with photon emission kinematics in strong magnetic field - Fomin, P.I.; Kholodov, R.I. (Вопросы атомной науки и техники, 2005)
The process of the photoproduction of the electron-positron pair with photon emission in strong magnetic field is
studied. A kinematics of the process is investigated and threshold values of energies and momenta of particles are found. Розглядається процес фотонародження електрон-позитронної пари з випромінюванням фотона в
сильному магнітному полі. Досліджено кінематику процесу і знайдено порогові значення енергій та
імпульсів часток. Рассматривается процесс фоторождения электрон-позитронной пары с испусканием фотона в сильном
магнитном поле. Исследована кинематика процесса и найдены пороговые значения энергий и импульсов
частиц.